ANALYSIS OF THE HEATING EFFECT ON HIGH PERFORMANCE MORTAR THROUGH 2D IMAGES OF X-RAY MICRO-TOMOGRAPHY AND SEM MICROSCOPY (Sciences & Technologie. B, Sciences de l'ingénieur, 2014)
The paper deals with the application of the X-ray micro-tomography technique to study high performance mortar notched test specimens first, after bending tests at room and hot conditions (700°C) and second, after just heating at 500°C. The scanning parameters were set to view all the test specimen transverse square section of 25 mmin side. In these conditions, a part of the material real porosity, supposed to be representative, was accessible. 2D and 3D reconstructed images were obtained and analysed. Hence, among the various microstructure parameters considered, the homogeneity of the porosity along the specimen was especially analysed through the pore area fraction parameter and discussed. A sensible increase in porosity of the areas surrounding the notch plane was observed and this result is probably related to the preparation of the specimen. The impact on the validity of bending tests performed on such notched specimens was also examined. Lastly the ability of this technique to evaluate temperature effect on porosity in these particular conditions was discussed in the light of complementary analysis of SEM micrographs.